Maghza Nasr Hamid Abu Zayd's Interpretation Concept As a Counter of Polygamy Pragmatism - Sam'ani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The objective of study is mainly to reveal the deep meaning of polygamous verses by using the theoretical approach of Nasr Hamid Abu Zayd's text study. As a critical Islamic thinker, Nasr produced many controversial views with classical thinkers, including interpreting the quranic polygamy verse. Nasr views the meaning of polygamy in quranic verse in its historical context as a limitation of the human relationship between men and women in the tradition of pre-Islamic Arabia. This initial meaning of that verse has a historical character and is only a starting point for understanding that verse. It is not the main message of the Qur'an. Nasr views the meaning of the quranic polygamy verse in the whole context of the Qur'an. The text's comprehensive context produces the original and significant meanings (magza). Then it also reveals the hidden dimension of meaning (al maskut 'anhu), the monogamy principle. By revealing this hidden meaning, it can counteract the pragmatic polygamists' statements, which are currently conducted on the pretext of religion. This study contributes to Qur'anic hermeneutics by highlighting the importance of the historical and social dimensions of religious texts in understanding verses that are often debated, such as polygamy verses.